Manufacturing Methods of Alloy Layers on Casting Surfaces - Szajnar, Jan; Wróbel, Tomasz; Dulska, Agnieszka (Journal of Casting & Materials Engineering, 2017)
In this paper, we presented the technology of layered castings based on the founding method of layer coating directly in the cast process known as the method of mold cavity preparation by monolithic or granular material of insert. Prepared castings consist of two fundamental parts: the base part and working part (layer). The base part of a layered casting is usually typical foundry material (i.e., pearlitic grey cast iron with flake graphite or ferritic-pearlitic carbon cast steel), whereas the dependence of an insert type (i.e., monolithic or granular) working part (layer) is suitably plated with ferritic and austenitic alloy steels or a layer from a Cr-base alloy. The ratio of thickness between the base and working part is between 8:1 and 10:1. The quality of the layered castings was evaluated on the basis of ultrasonic non-destructive testing, structure, and selected usable property research. According to work out technology, the prepared layered castings can work in conditions that require high heat resistance and/or corrosion resistance from the working surface layer of an element in a medium of industrial water, for example. Moreover, in the case of applying an insert based on Cr-base alloy powder on the working surface layer, it is possible to obtain high hardness and abrasive wear resistance.